1999
DOI: 10.1016/s0163-6383(00)00018-7
|View full text |Cite
|
Sign up to set email alerts
|

Does infancy matter? predicting social behavior from infant temperament

Abstract: In this essay we argue that infant temperament, defined as behavioral styles that appear early in life as a direct result of neurobiological factors, plays a significant role in the development and expression of social behavior. Temperament may be studied using a typological or dimensional approach and the relations between early temperament and later behavior can be examined in terms of homotypic or heterotypic continuity. The implication of each of these approaches for understanding the influence of infant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…They also noticed that their children were less adaptable to new situations, had fewer pleasurable mood states and irregular bodily rhythms compared to healthy controls. As temperamental difficulties in toddlerhood were reported to be persisting into infancy, results like these add to previous suggestions that infant temperament can be predictive of later social behaviour (Biederman et al 1995b;Fox and Henderson 1999).…”
Section: Temperament Factors and Sleep Disturbancessupporting
confidence: 82%
“…They also noticed that their children were less adaptable to new situations, had fewer pleasurable mood states and irregular bodily rhythms compared to healthy controls. As temperamental difficulties in toddlerhood were reported to be persisting into infancy, results like these add to previous suggestions that infant temperament can be predictive of later social behaviour (Biederman et al 1995b;Fox and Henderson 1999).…”
Section: Temperament Factors and Sleep Disturbancessupporting
confidence: 82%
“…However, the social perceptiveness of victims was not significantly different from socially adjusted children, suggesting that children's victim status is not the result of deficits in this area. Rather, previous research has found that infants with high maternal ratings of withdrawal negativity to be at low risk of developing aggressive behaviors later in childhood (Rothbart et al 1994), while greater infant withdrawal negativity has been associated with greater childhood shyness, withdrawal, and fear (Fox and Henderson 1999), qualities characteristic of victims (Haynie et al 2001;Perren and Alsaker 2006). Because of these emotional characteristics, non-aggressive victims may be viewed by other children as easy targets for aggression, whereas aggressive victims' angry, impulsive behavior may be provocative of peer aggression.…”
Section: Discussionmentioning
confidence: 94%
“…For example, one study has shown that FAA assessed in infants was significantly associated with behavioral inhibition assessed in 4-year old toddlers over 3 years after the initial assessment 33 . Similarly, FAA asymmetry measures obtained in infants who were 10 and 24 months old prospectively predicted mother-rated toddler internalizing and externalizing behaviors when the children were 30 months old 34 .…”
Section: Introductionmentioning
confidence: 99%